Genetic and phenotypic impacts of calf gender on productive and reproductive traits in Friesian cattle under Egyptian farm conditions - Genena, Shereen K.; ElSawy , Mohamed H. (Journal of Advanced Veterinary Research, 2024)
This study was implemented to evaluate utilizing sexed semen that favors female births for enhancing milk production and herd replacements. 4913 calf records from 1047 Friesian cows between 1975 and 2020 at Sakha Farm were analyzed to estimate the impacts of calf gender and some environmental factors on the productive traits: lactation period (LP), total (TMY) and 305-day (305MY) milk yields and reproductive traits: age at first calving (AFC); gestation length (GL); days open (DO) and calving interval (CI). Fixed effects were parity; calving year and season (SC). Genetic (rg) and phenotypic (rp) correlations were estimated using BLUPF90 software. Results showed highly significant effects (P<0.001) of the fixed factors on all studied traits, except SC (P< 0.05) on LP and TMY, (P< 0.01) on 305MY and DO, but non-significant effects on reproductive traits. Calf gender presented strongly meaningful effects (P<0.001) regarding CI plus (P<0.05) for other traits, except AFC and genders on DO. Moderate positive rg estimates were found from 0.29 to 0.32 for female births with productive traits; weak values were found with reproductive traits, except 0.14 with GL. The corresponding rp estimates ranged from 0.26 to 0.36 with productive traits; from 0.11 to 0.19 with reproductive traits, except for weak values with DO and CI. It can be strongly encouraged to alter calf gender in females to diminish the generation interval, maximize milk production, and increase the genetic superiority of replacements.